Assessing the unemployment rate as a mediator between SMEs and economic growth - Cahyadin, Malik; Irianto, Heru; Ertimi, Basem (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
Economic growth and unemployment reduction in developing countries can be strengthened by improving the business quality of SMEs. As SMEs dominate Indonesia’s industrial structure, this study examines their relationship with economic growth, with unemployment rates as a moderating variable, in West Java, Central Java, and East Java from 2015 to 2022. Using Structural Equation Modeling (SEM) on 96 observations, the findings reveal that the number of SME business units has a significant negative impact on the unemployment rate, whereas total assets have a positive impact. A higher asset value enhances the capacity for modernization and digitalization, which, in turn, reduces labor absorption and potentially increases unemployment. Additionally, a decline in the unemployment rate positively influences economic growth, which is consistent with Okun’s Law, though with a relatively low magnitude. These findings highlight the need for government policies to facilitate SME business development by improving production standards, expanding access to business capital, and enhancing market reach. This approach aligns with the UMKM Naik Kelas (SME Scale-Up) program, which aims to promote sustainable SME growth and economic resilience.